An Analysis of French-Indonesian Translation Strategies in Guillaume Musso's Novel Seras-tu La? - Achadiat, Sandya Najmi Putri; Gumilar, Dudung; Widawati, Rika (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
Literary translation is a form of cultural exchange, with figurative language serving as a bridge that transfer the distinctive values, norms, and perspectives from the source language to the target language. However, meaning equivalence in the translation of figurative language remains suboptimal. This study aims to 1) describe how figurative language in the novel Seras-tu Là ? is translated from French into Indonesian; and 2) determine whether the translation strategies used are able to maintain the figurative language and emotional nuances in the target text. This research employs a descriptive qualitative approach. The data sources are the French version of the novel Seras-tu Là ? and its Indonesian translation. Data were collected using document analysis techniques through the observe-and-note method. The results show that 1) figurative language in the novel is predominantly translated using dynamic equivalence strategies to maintain acceptability in the target language; and 2) the translation strategies used are largely able to preserve the figurative language and its emotional nuances, although they sometimes reduce the literal meaning of certain diction. Thus, dynamic equivalence strategies clearly dominate the translation of figurative language in this novel and are able to maintain Musso’s distinctive style and emotional nuance in most of the data.